How many ways can we do to remain in Jesus, in God? What is the measure to know that Jesus remains in us? - Nguyen, Duc Trong (Khoa Học Công Giáo và Đời Sống, 2021)
How can a visible creature be conformed to the transcendent spiritual, invisible God? Saint John shows us three ways that we can remain in Jesus' love: obeying His word, carrying out his commandments, sticking to him like a branch attached to the stem of a vine. From these three ways, we realize that Jesus' presence in our lives is fruitful: a holy life, you will be satisfied whatever you ask, we become His brothers in The spirit.